A metagenomic lens into endosphere microbial communities, promises and discoveries. (14th December 2022) - Adeleke, Bartholomew Saanu; Muller, Daniel; Babalola, Olubukola Oluranti
Abstract: The word endosphere represents the internal tissues of plants harboring diverse microbes capable of producing active biological products for various biotechnological and agricultural applications. The discreet standalone genes and interdependent association of microbial endophytes with plants can be an underlining factor in predicting their ecological functions. Yet-to-be cultured endophytic microbes have geared the invention of metagenomics in various environmental studies to determine their structural diversity and functional genes with novel attributes. This review presents an overview of the general concept of metagenomics in microbial endophytic studies. First, the endosphere microbial communities were introduced, followed by metagenomic insights in endosphere biology, a promising technology. Also, the major application of metagenomics and a short brief on DNA stable isotope probing in determining functions and metabolic pathways of microbial metagenome were highlighted. Therefore, the use of metagenomics promise to provide answers to yet-to-be-cultured microbes by unraveling their diversity, functional attributes, and metabolic pathways with prospects in integrated and sustainable agriculture.